The Aftereffects of IMF Interventions on International Trade: Lessons from the Indian Experience - Sisir Ranjan Dash, Brijlal Mallik, Bishwaranjan Purohit, Shyamali Satpathy (International Journal of Modern Agriculture, 2020)
Loans from IMF in the form of SDRs are always conditional and the conditions are to implement structural adjustments in the economy of beneficiary nations. In this context, one of the priority areas of reforms prescribed by IMF to India in its structural adjustments was in the context of exchange rate and trade policy .So, the question is that whether IMF interventions actually have significant aftereffects on international trade or not. In order to answer this, the present study has been initiated and by implementing t-Test: Paired Two Sample for Means it has been found that there is a significant difference in exports, imports and total trade of goods and services before and after IMF interventions. But, an interesting finding of the study is that the IMF interventions though have the ability to significantly boost exports, it has also significant effects on improvements of imports. So, favorable effects of boost in exports will finally be neutralized by adverse effects of improvements in imports and the ratio between imports and exports may remain insignificant even with IMF interventions..